UJI EFEKTIVITAS SEDIAAN KRIM EKSTRAK ETANOL DAUN AFRIKA (Vernonia amygdalina Del.) TERHADAP BAKTERI Propionibacterium acnes. - Atriana Zain; Maulana, Maulana Zulkarnain Imansyah (Akademi Farmasi Yamasi Makassar, 2023)
African leaves (Vernonia amygdalina Del.) or what used to be called